Determinants of Capital Structure in Mining Companies Listed on the Indonesia Stock Exchange - Damayanti Damayanti; Melina Ika Jayanti (Cita konsultindo, 2023)
This study aimed to prove and explain the analysis of the factors affecting the capital structure of mining companies listed on the Indonesia Stock Exchange. The study used the sampling technique with purposive sampling. It took a sample of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, with a sample of 15 companies. Furthermore, the technique of data analysis utilized multiple linear regression analysis. The outcomes showed that profitability had no significant negative impact on the capital structure of mining companies listed on the Indonesia Stock Exchange; on the other side, liquidity had a significant negative impact on the capital structure of them. Meanwhile, asset structure and sales growth had no significant positive impact on the capital structure of mining companies listed on the Indonesia Stock Exchange. In addition, The adjusted R2 score is 0.339 indicating that the variation of the four independent variables, ROE, CR, AG and SG, can explain 33.9% of the variation, and factors outside this study model explain the remaining 66.1%.